Improvement Approach for Matching PV-array and Inverter of Grid Connected PV Systems Verified by a Case Study - Moien A. Omar; Marwan M. Mahmoud (International Journal of Renewable Energy Development, 2021)
Correct matching between PV array and inverter improves the inverter efficiency, increases the annual produced energy, decreases the clipping losses of the inverter, and prevent to a large extent the inverter frequent shut downs during clear sunny days of high solar radiation and low ambient temperature. Therefore, this paper presents a new methodology for selecting the appropriate peak power of the PV array with respect to the inverter output AC rated power taking into account the local daily distribution of solar radiation and ambient temperature. In addition, the proposed methodology specifies the appropriate number of PV modules in each string and the number of parallel strings connected to the input of the inverteraccording to its specifications and to PV cell temperature. Mathematically modeling of system parameters and components are presented and used in the simulation to investigate the different scenarios. The paper presents also a case study using simulation to find the optimal matching parameters of a PV array connected to an inverter with the specifications: 6 kW rated output power, an input mpp voltage range of 333-500 V, 6.2 kW maximum input DC power, and an output AC voltage of 230 Vrms. Considering the local climate conditions in West Bank, the simulation resulted a peak power of 7 kW for the PV array, which is greater than the inverter output power by the factor 1.16. In addition, the obtained PV array consists of two parallel strings each includes 12 PV modules  connected in series  while each PV module is rated at 290 W. The output voltage of the PV arrayvaries between 359 V to 564 Vat minimum and maximum temperature of 10 ˚C to 70 ˚C respectively. This PV array-inverter combination resulted by simulation an annual yield of 1600 kWh/kWp and an energy of 11197 kWh which corresponds to an energy gain of 1591 kWh/year more than using a PV array with a peak power of 6 kW as the inverter rated power.